THE ELECTRON MICROSCOPIC LOCALIZATION OF CHOLINESTERASE ACTIVITY IN THE CENTRAL NERVOUS SYSTEM OF AN INSECT, PERIPLANET A AMERICANAL. - Smith, David S. (The Rockefeller University Press, 1965)

(untitled)
The distribution of esterase activity in the last abdominal ganglion, the connectives and the cereal nerves of the cockroach Periplaneta americana has been investigated cytochemically. Activity of an unspecific eserine-insensitive esterase (or esterases) has been found in glial elements in these regions of the nerve cord. In addition, sites of cholinesterase (eserine-sensitive) activity have been found in association with (a) the glial sheaths of the axons in the cereal nerves and connectives, (b) the glial folds encapsulating the neuron perikarya in the ganglion, and (c) in localized areas along the membranes of axon branches within the neuropile, often flanked by focal clusters of synaptic vesicles. These results are discussed with particular reference to the previously reported insensitivity of the insect nerve cord to applied acetylcholine, and to the probable existence of a cholinergic synaptic mechanism in the central nervous system of this insect.